The Effect of Online Customer Review and Online Customer Rating on Purchase Decision with Brand Image as Mediation on Shopee Marketplace in Medan City - Pasaribu, Wilson; Sembiring, Beby Karina Fawzeea; Rini, Endang Sulistya (Journal of Business Management, 2025)
Shopee is one of the online shopping places in Indonesia that allows individuals, small shops, and brands to make online transactions. The Brand Image owned by Shopee is already known to the Indonesian people compared to several other e-commerce platforms. The purpose of this study is to analyze "The Effect of Online Customer Review and Online Customer Rating on Purchase Decision with Brand Image as mediation on Shopee Marketplace in Medan City". The data collected in this study are primary data and secondary data, which are collected through data collection instruments in the form of questionnaires, interviews and documentation studies. The sample in this study was 150 respondents. This study uses quantitative data, with the Partial Least Square (PLS) method. The test results show that partially brand image has a significant effect on purchase decision, online customer review has a significant effect on brand image, online customer review does not have a significant effect on purchase decision, online customer rating has a significant effect on brand image, online customer rating has a significant effect on purchase decision. Brand image as an intervening variable does not have a significant impact in increasing the influence of online customer rating on purchase decision. Brand image as an intervening variable as an intervening variable has a significant impact between the influence of online customer review on purchase decision.